Schedule for personality assessment from notes and documents (SPAN‐DOC): Preliminary validation, links to the ICD‐11 classification of personality disorder, and use in eating disorders. (May 2016) - Kim, Youl‐Ri; Tyrer, Peter; Lee, Hong‐Seock; Kim, Sung‐Gon; Connan, Frances; Kinnaird, Emma; Olajide, Kike; Crawford, Mike
Abstract: Background: The underlying core of personality is insufficiently assessed by any single instrument. This has led to the development of instruments adapted for written records in the assessment of personality disorder. Aims: To test the construct validity and inter‐rater reliability of a new personality assessment method. Method: This study (four parts) assessed the construct validity of the Schedule for Personality Assessment from Notes and Documents (SPAN‐DOC), a dimensional assessment from clinical records. We examined inter‐rater reliability using case vignettes (Part 1) and convergent validity in three ways: by comparison with NEO Five‐Factor Inventory in 130 Korean patients (Part 2), with agreed ICD‐11 personality severity levels in two populations (Part 3) and determining its use in assessing the personality status in 90 British patients with eating disorders (Part 4). Results: Internal consistency (alpha = .90) and inter‐rater reliability (intraclass correlation coefficient ≥ .88) were satisfactory. Each factor in the five‐factor model of personality was correlated with conceptually valid SPAN‐DOC variables. The SPAN‐DOC domain traits in those with eating disorders were categorized into 3 clusters: self‐aggrandisement, emotionally unstable, and anxious/dependent. Conclusions: This study provides preliminary support for the usefulness of SPAN‐DOC in the assessment of personality disorder. Copyright © 2016 John Wiley & Sons, Ltd.